An undescribed species of velvet worm from Chiapas, Mexico (Onychophora: Peripatidae) (UNED Research Journal, 2018)
Onychophoran worms are considered "living fossils" because their basic body structure has changed little in 500 million years. Only two species have been properly recorded from Mexico: Macroperipatus perrieri from Veracruz, and Oroperipatus eisenii from Nayarit. Here we report an undescribed species of Oroperipatus from Tuxtla Gutiérrez, Chiapas. Males, which are rarer, smaller and reddish than females, are 3-4cm long and have 24-25 leg pairs (N=6). Females are 4-7,5cm long and have 28-29 pairs (N=19). We propose the common name "Tuxtla Brownish Purple Velvet Worm" to help study and protect the species until it receives formal description. This new record expands the known distribution of the phylum in Mexico from the evergreen forest of Veracruz to the deciduous forest of Tuxtla (400Km).
Keywords: extension of geographic range; new locality; new undescribed species; velvet worm; urban onychophorans.